Scientific-theoretical foundations of the negative impact of social networks on the moral and ethical upbringing of youth - Ugli , Madraximov Alisher Usubjon (Goodwood Publishing, 2024)
Purpose: This study aims to examine the impact of social networks on the moral and ethical development of young people in the era of globalization. It explores how social media platforms serve not only as tools for communication and information exchange but also as powerful agents of influence shaping young individuals' values, attitudes, and perceptions Methodology/approach: The article adopts a qualitative descriptive approach, drawing on literature analysis, case studies, and prior empirical findings on social media usage among youth. The study also maps the historical development of social networks, tracing their evolution from traditional offline communities to the present-day digital environment. Results/findings: Findings reveal that social networks play a dual role in youth education and character building. While they provide opportunities for knowledge sharing, cultural exchange, and promotion of spiritual and national values, they also expose youth to misinformation, cyberbullying, harmful content, and value distortion. The research identifies critical phases where social networks significantly influence moral development, highlighting the risks of unfiltered exposure to digital platforms Conclutions: Social networks are shaping the ethics and behavior of younger generations more profoundly than traditional institutions. Proper guidance, digital literacy programs, and value-based content creation are necessary to harness social media’s benefits while mitigating its negative effects. Limitations: The study relies on secondary data and literature-based analysis, lacking primary empirical data from large-scale youth surveys. Contribution: This research provides scientific recommendations for policymakers, educators, and parents on fostering positive digital environments that strengthen ethical, spiritual, and national values among youth.